THE IDEAS OF JOURNALISTIC ETHICS BASED ON PANCASILA FOR MULTICULTURAL SOCIETY - Sugeng, Sugeng; Hadinata, Fristian (UI Scholars Hub, 2024)
This paper aims to show that journalistic code of ethics based on Pancasila is strongly related to multiculturalism morality as both emphasize inclusive ideas, respect for diversity, and the awareness of unity in diversity. The writers use descriptive qualitative library research in the field of philosophy to show meaning and objectively reveal philosophical essence. This method includes collecting and analyzing criticism of relevant literature related to multiculturalism, philosophy, journalistic ethics, and cyber media reporting. The result shows that the development of the internet technology has changed the way society live, and it has affected their preferences towards the elements of mass communication. This media ecological evolution happens worldwide, including in Indonesia. The internet technology, in its various forms, has determined how society communicate interpersonally, among groups, and as a mass. By integrating the values of Pancasila into the inclusive journalistic practices, the media can serve as an agent that strengthens multiculturalism awareness, encourages unity, and promotes equality and fairness for all citizens. Through reporting that highlights respect, unity, and equality, the media can contribute positively to a strong, united, and civilized society, while at the same time strengthening the social bonding among citizens. The Active Tolerance Principal has created a framework that ensures that journalism not only avoids harming certain groups of people through biased news coverage, but can also attempt to reinforce understanding, dialogs, and peace among different groups which is a crucial step in creating a responsible and inclusive journalism which is also oriented towards the public interest.